A hole in the world : finding hope in rituals of grief and healing - Opelt, Amanda Held (Worthy, 2022)
"Generations past have embraced a robust array of rituals and customs surrounding death and bereavement. When did we forget how to grieve well? When Amanda Held Opelt suffered a season of loss-including three miscarriages and the death of her grandmother and culminating in the unexpected death of her sister, New York Times bestselling writer Rachel Held Evans-she was faced with sorrow she didn't know to face. And through her career as an international aid worker, she traveled to some of the world's most troubled regions, devastated by war, natural disasters, and disease. In the wake of these losses and exposure to trauma, Opelt struggled to process her grief and accept the reality of her pain and the pain in the world. She also wrestled with some unexpectedly difficult questions: What does it mean to truly grieve and to grieve well? Why is it so hard to move on? Why didn't my faith prepare me for this kind of pain? Does the Bible really speak to the heart of sorrow? What am I supposed to do now? Her search for a way to process her grief led her to seek wisdom about how other people have made it through, and she found that generations past embraced rituals that served as vessels for pain and aided in the process of grieving and healing. Today, many of these traditions have been lost as religious practice declines, cultures amalgamate, death is sanitized, and pain is averted. In this raw and authentic memoir of bereavement, Opelt explores the history of human grief practices and how previous generations have journeyed through periods of suffering. She explores grief rituals and customs from various cultures, including: --the Irish tradition of keening, or wailing in grief, which teaches her that healing can only begin when we dive headfirst into our grief. --the Victorian tradition of post-mortem photographs and how we struggle to recall a loved one as they were. --the Jewish tradition of sitting shiva, which reminds her to rest in the strength of her community even when God feels absent. --the tradition of mourning clothing, which set the bereaved apart in society for a time, allowing them space honor their grief. As Opelt explores each bereavement practice, it allows her to utilize these rituals as a framework for processing their own pain. She shares how, in spite of her doubt and anger, God met her in the midst of sorrow and grieved along with her. This book is a testament to the idea that when we carefully and honestly attend to our losses, we are able to expand our capacity for love, faith, and healing"--